Analysis of Climate Change Scenarios Using the LARS-WG 8 Model Based on Precipitation and Temperature Trends - Hadi, Saad H.; Alwan, Husam H.; Al-Mohammed, Fadhil M. (Salehan Institute of Higher Education, 2024)
Global food production and water distribution are at risk due to increasing temperatures and changing precipitation trends. The main objective of the study was to analyze the climate trend and future projections in seven stations in southern Iraq. The period (1981–2020) was designated as a base period. The periods (2021-2040) and (2041-2060) were defined as the future two periods. The Mann-Kendall trend test was employed to assess trends utilizing XLSTAT. The study employed the most recent version of the LARS-WG 8 model to forecast climate change by using three GCMs (ACCES-ESM1-5, HadGEM3-GC31-LL, and MRI-ESM2-0). These simulations are based on two scenarios (SSP-245 and SSP-585). The statistical indicators provided support for the outcomes of model calibration and validation, demonstrating its competence and reliability. The results of this analysis indicate that there is a non-significant increase in precipitation and a considerable increase in both maximum and minimum temperatures during the period (1981-2060). The downscaled result reveals an increase in monsoon precipitation in the range of 2.233-2.831 mm under SSP-245 and SSP-585, respectively, compared with the base periods 1981-2020 during the Near Future and 1.988-2.543 mm during the mid-future. Also, annual maximum/minimum temperature increases in the range of (1.156-1.549 °C) and (1.486-1.770 °C) during the Near Future. (2.095-2.892 °C) and (1.486-1.770 °C) during the mid-future, respectively, for SSP-245 and SSP-585. These outcomes can enhance understanding to develop strategies for mitigating and adapting to these impacts. Doi: 10.28991/CEJ-2024-010-12-014 Full Text: PDF